2021
DOI: 10.1002/jclp.23266
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the association of eating disorder features to suicide ideation and attempts

Abstract: Objective We examine the relationships of eight eating disorder (ED) features to histories of suicide ideation and suicide attempts. Method Participants were 387 adults (62% female, mean age = 36 years) recruited via an online platform, and oversampled for the presence of ED features, who completed standardized self‐report measures of study variables. Results Different ED features predicted suicide ideation versus attempts. Specifically, Restrictive Eating (d = 0.44), Purging (d = 0.30), and Body Dissatisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
(71 reference statements)
1
2
0
Order By: Relevance
“…Regarding specific ED symptoms, Hunt and Levinson (2021) found that fasting and purging exhibited direct associations with suicidal ideation. Shahnaz and Klonsky (2021) reported similar findings. Overall in the work conducted to date, purging and restricting appear to be more strongly associated with suicidality as compared to other ED behaviors such as binge eating.…”
Section: Introductionsupporting
confidence: 68%
“…Regarding specific ED symptoms, Hunt and Levinson (2021) found that fasting and purging exhibited direct associations with suicidal ideation. Shahnaz and Klonsky (2021) reported similar findings. Overall in the work conducted to date, purging and restricting appear to be more strongly associated with suicidality as compared to other ED behaviors such as binge eating.…”
Section: Introductionsupporting
confidence: 68%
“…An analysis of 36,171 adults found that a lifetime history of suicide attempt was associated with earlier onset of bulimia nervosa and longer duration of anorexia nervosa (Udo et al, 2019). A study of 387 adults found that excessive exercise, muscle building, and restrictive eating were common among individuals with a history of suicide attempt (Shahnaz & Klonsky, 2021). These studies were however cross‐sectional and did not address adolescents (Shahnaz & Klonsky, 2021; Udo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A study of 387 adults found that excessive exercise, muscle building, and restrictive eating were common among individuals with a history of suicide attempt (Shahnaz & Klonsky, 2021). These studies were however cross‐sectional and did not address adolescents (Shahnaz & Klonsky, 2021; Udo et al, 2019). The objective of this hypothesis‐testing study was to determine the association between adolescent suicide attempts and the subsequent risk of eating disorder hospitalization.…”
Section: Introductionmentioning
confidence: 99%